Proceso de atención nutricional en paciente masculino de 67 años de edad con diabetes mellitus tipo 2 y sobrepeso. - Cobeña Acosta, Lisseth Rashel (2022)
In the present clinical case we find a 67 years old patient who attends a medical visit due to altered glucosa levels, for which he has bodily discomfotr and who in turn presents poliuria and polyphagia due to glucosa levels in elevated blood also refers that he has been whith this clinical cadre associated whith it for a week, the patient is also overweight. The patient was assessed by anthropometric, biochemical assessmet, food consumption or also called a twenty four hour reminder plus the clinical signs present. Through anthropometric assessment, the 67 years old patient weighs 59kg and is 1.50 cm tal whith a IMC of 26.2kg/m2 overweight. In ther biochemical evaluation we found glucosa of 258mg/dl (hyperglycemia). He already refers to a pathological history of type II diabetes mellitus plus being overweight, with a family pathological history: diabetic mother and father with renal insufficiency, the patient indicates that for 1 year he has not drunk any alcoholic beverages or smoked, he does not perform any type of physical activity for the moment. The main objective in this case study is to improve their nutritional status since at the time of their assessment it indicates that they are overweight and hyperglycemic.